Próba analizy prawnokarnej konstrukcji umyślności - Rodzynkiewicz, Mateusz (Wydział Prawa i Administracji UAM, 1990)
The article indicates incoherencies in Art. 7 § 1 of the Penal Code of 1969. The notion of intentionality de lege lata goes beyond linguistic intuitions and is of eclectic character. Discussing the form of intentionality known as dolus eventualis the author supports W. Wolter's theory of neutrality, stressing its conclusion according to which dolus eventualis is only a fiction of intention. The author critically presents a new approach to intentionality put forth by K. Buchała and A. Zoll. Analizing the question of „dolus directus" the author indicates that also in that case lawyers create the fiction of intentionality. Namely, they refer „wanting" to the necessary side-effect of the perpetrator's behaviour. There is an error in this reasoning, for one may „want" something that is the aim of one's behaviour or a means necessary to the attainment of that aim, and not something that is „disconnected" from that aim, being only a side-effect of one's behaviour. The author assumes that in the latter case there is no intention but the neutrality of will related to the side-effect understood by the perpetrator as necessary, just as in the case of dolus eventualis in W. Wolter's conception where the neutrality of will is referred to the side-effect understood by the perpetrator as possible. In the last part of the article the author formulates two versions of defining intentionality de lege ferenda. The first refers to the contents of Art. 7 § 1 of the Penal Code, the second to the proposal put forth by K. Buchała and A. Zoll. Finally the author points to the methodological advantages of his formula in the context of so-called directional offences.
An attempt of the analysis of the penal law construction of intentionality